2021
DOI: 10.18632/aging.203524
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of STAT3 overexpression plasmid mediated through recombinant lentivirus promotes differentiation of bone marrow mesenchymal stem cells into neural cells in fetal rats with spina bifida aperta

Abstract: We investigated the influence of signal transducer and activator of transcription-3 (STAT3) on the spinal cord tissue grafts of rat fetuses with spina bifida aperta. In particular, we hoped to identify whether transfection of the STAT3 overexpression plasmid increases the survival of spinal cord transplantation in order to improve therapeutic efficacy. The fetal rat model of spina bifida aperta was established using retinoic acid and treated with a microsurgical injection of bone marrow mesenchymal stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Hence, STAT3 overexpression in MSCs is a promising strategy for cell-based therapy. Consistent with this notion, transplanted BMSCs overexpressing STAT3 via recombinant lentivirus infection promoted the survival of fetal rats with spina bifida aperta (SBA), and this effect was associated with reduced BMSC apoptosis, enhanced BMSC survival, and increased neural marker expression [ 165 ]. Overexpression of the transcription factor nuclear receptor-related factor 1 (Nurr1), a member of the orphan nuclear receptor family implicated in dopaminergic neuron development and maturation, accelerated the dopaminergic differentiation of UC-MSCs [ 166 ] and BMSCs [ 167 ] and promoted the recovery of a rat model of Parkinson's disease (PD).…”
Section: Selecting Appropriate Genes For Transductionmentioning
confidence: 97%
“…Hence, STAT3 overexpression in MSCs is a promising strategy for cell-based therapy. Consistent with this notion, transplanted BMSCs overexpressing STAT3 via recombinant lentivirus infection promoted the survival of fetal rats with spina bifida aperta (SBA), and this effect was associated with reduced BMSC apoptosis, enhanced BMSC survival, and increased neural marker expression [ 165 ]. Overexpression of the transcription factor nuclear receptor-related factor 1 (Nurr1), a member of the orphan nuclear receptor family implicated in dopaminergic neuron development and maturation, accelerated the dopaminergic differentiation of UC-MSCs [ 166 ] and BMSCs [ 167 ] and promoted the recovery of a rat model of Parkinson's disease (PD).…”
Section: Selecting Appropriate Genes For Transductionmentioning
confidence: 97%
“…Total RNA was extracted from cells and tissues using TRIzol reagent under RNase-free conditions, according to the manufacturer's protocol. All quali ed RNA was reverse transcribed using random primers and stem-loop primers in the RT Reagent Kit system [15]. β-Actin was used as the housekeeping gene.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Though the JAK2/STAT3 pathway upregulated adipogenesis and restricted osteogenesis in a leptindependent manner, STAT3 may enhance MSCs' migration ability to increase their therapeutic efficacy [196]. It is suggested that the STAT3 pathway can be involved in inducing differentiation of BMSCs into neural cells [197] and have an antisenescence role [198]. Taken together, maintaining the correct function of STAT3 is an important issue for aging homeostasis in MSCs.…”
Section: Miscellaneous Signalingmentioning
confidence: 99%